Motion Graphic tentang Masjid Agung Pondok Tinggi Berbasis Android - syahrul, yasermi (Teknomatika, 2017)
Local cultural heritage has contributed to being studied in search of solutions in the effort to overcome the problems encountered in the past. The problem of diversity of cultural heritage is considered to have no relevance to the present let alone for the future. The Great Mosque of Pondok Tinggi is one of the historic physical heritage (tengible). The making of motion graphic serves to help in promoting and introducing the Grand Mosque of Pondok Tinggi as a cultural heritage of the past and introduction to tourists, as a means of information to increase the number of tourists to Sungai Penuh Town. Methods of data collection carried out with the stages of observation, interviews, and literature study. Then proceed with the methodology used in the multimedia production process is a 3 stage production flow that is pre production, production, and post production. The results obtained have met the good criteria as a medium of information about the Great Mosque Pondok Tinggi to be delivered to the public or tourists.Keywords— Mosque, Design, Cultural Heritage, Motion Graphic